A fauna de parasitas de Serrasalmus rhombeus (Linneaus, 1776) (Characiformes: Characidae) de lagos de várzea da Amazônia central - Lima, Mariel Acácio de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2010)
The parasites fauna of 45 Serrasalmus rhombeus colleted in dry season from six floodplain lakes of the Solimões River, in December of 2007, were studied. Seventeen were males and 28 females and 44 (97.7%) of fish were parasitized. A total of 2017 parasites were collected, 17 species of Monogenoidea: Amphithecium diclonophallum; A. falcatum; A. muricatum; Anacanthorus amazonicus; A. jegui; A. scapanus; A. sciponophalus; A. serrasalmi; Anacanthorus sp.1, Anacanthorus sp.2, Anacanthorus sp.3, Anacanthorus sp.4, Anacanthorus sp.5. Notothecium cyphophalum; Notothecium sp.1; Notozothecium aegidatum; N. teinodendrum. Two species of Digenea, Clinostomum sp. e metacercariae. One species of Nematoda, Procamallanus (S) inopinatus. Two species of Copepoda, Ergasilus yumaricus e Myracetyma piraya and one of Branchiura, Argulus chicomendesi. The parasites were most abundant. Procamallanus (S) inopinatus, Ergasilus yumaricus and A. chicomendesi are new records of occurrence in S. rhombeus. Thirty-five S. rhombeus were infected with cysts of metacercariae of digenetic in the skin. Fish that had the highest numbers of parasites were the Campina and Ananá lakes. The prevalence of fish from all lakes studied was 100%, except in Lake Maraca which was 90%. The number of parasites in the males of S. rhombeus was higher than in females. Larger fish had higher number of parasites.
Keywords: Piranha preta; Parasitofauna; Serrasalmus rhombeus